Microtus (Microtus) arvalis - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Microtus (Microtus) arvalis (Pallas 1778) [Mus] arvalis Pallas 1778, Nova Spec. Quad. Glir. Ord.: 78. Type Locality: Russia, Leningrad Oblast, Pushkin-town (as restricted by neotype selection by Malygin and Yatsenko, 1986; formerly as " Germany," e.g., Ellerman and Morrison-Scott, 1951). Vernacular Names: Common Vole. Synonyms: Microtus (Microtus) albus (Bechstein 1801); Microtus (Microtus) arvensis (Schinz 1840); Microtus (Microtus) angularis Miller 1908; Microtus (Microtus) assimilis (Rörig and Börner 1905); Microtus (Microtus) assimilis Miller 1912; Microtus (Microtus) asturianus Miller 1908; Microtus (Microtus) ater (de Sélys Longchamps 1845); Microtus (Microtus) brevirostris Ognev 1924; Microtus (Microtus) calypsus Montagu 1923; Microtus (Microtus) campestris (Blasius 1853); Microtus (Microtus) caucasicus Satunin 1896; Microtus (Microtus) cimbricus Stein 1931; Microtus (Microtus) contigua (Rörig and Börner 1905); Microtus (Microtus) corneri Hinton 1910; Microtus (Microtus) cunicularius (Ray 1847); Microtus (Microtus) depressa (Rörig and Börig 1905); Microtus (Microtus) depressa Miller 1912; Microtus (Microtus) duplicatus Rörig and Börner 1905; Microtus (Microtus) duplicatus Miller 1912; Microtus (Microtus) flava (Fatio 1905); Microtus (Microtus) fulva (Fatio 1869); Microtus (Microtus) fulvus Geoffroy 1803; Microtus (Microtus) fulvus (Miller 1912); Microtus (Microtus) galliardi (Fatio 1905); Microtus (Microtus) ghalgai (Krassovsky 1929); Microtus (Microtus) grandis Martino and Martino 1948; Microtus (Microtus) gudauricus Ognev 1929; Microtus (Microtus) hawelkae Bolkay 1925; Microtus (Microtus) heptneri Hamar 1963; Microtus (Microtus) hyrcania Goodwin 1940; Microtus (Microtus) igmanensis Bolkay 1919; Microtus (Microtus) incertus (de Sélys Longchamps 1841); Microtus (Microtus) incognitus Stein 1931; Microtus (Microtus) iphigeniae Heptner 1946; Microtus (Microtus) khorkoutensis Goodwin 1940; Microtus (Microtus) macrocranius Ognev 1924; Microtus (Microtus) meldensis Delost 1955; Microtus (Microtus) meridianus ...